2013
DOI: 10.1021/nl401870d
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli-Based Biophotonic Waveguides

Abstract: The rapid progresses in biological and biomedical applications with optical interfaces have motivated an ever-increasing demand for biocompatible and disposable photonic components. Generally, these biophotonic components are first integrated with biocompatible materials and then interfaced with biological samples, such as living cells, for biological use. Therefore, direct formation of biophotonic components using living cells is greatly desired because the cells would serve simultaneously as samples and opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 17 publications
0
87
1
Order By: Relevance
“…Many hydrogels are amenable to cell encapsulation which can then be used for light-mediated sensing or drug release [4,8]. Other research into biocompatible optical waveguides have utilized a variety of other materials including cellulose [9], silicone [10], agarose [8], and even bacterial cells [11], but due to high propagation losses, these materials have not seen rapid adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Many hydrogels are amenable to cell encapsulation which can then be used for light-mediated sensing or drug release [4,8]. Other research into biocompatible optical waveguides have utilized a variety of other materials including cellulose [9], silicone [10], agarose [8], and even bacterial cells [11], but due to high propagation losses, these materials have not seen rapid adoption.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a linear array of Escherichia coli aligned by optical forces could guide light [135]. Although bacteria would not be considered applicable to implantable devices, this work suggests the possibility of forming an optical waveguide in situ inside biological tissue by self-assembly of human cells or biocompatible particles.…”
Section: Bio-derived Materials Waveguidesmentioning
confidence: 96%
“…To date, various optical waveguides have been fabricated using natural materials such as silk [34], cellulose [46] and bacteria cells [47]. For example, bio-derived cellulose polymers can be thermally drawn to form a core-cladding fiber structure, with some cellulose powders in between to form a hollow channel for potential drug delivery [46].…”
Section: Materials and Synthesismentioning
confidence: 99%
“…These cellulose fibers are fully dissolved after 1-day immersion in aqueous solutions and during the dissolution, the light transmittance increases with water intake. Optical waveguides can also be formed from bacterial cells (e.g., Escherichia coli, propagation loss ~0.23 dB/μm [47]), and their optical losses are needed to be further reduced for practical uses.…”
Section: Materials and Synthesismentioning
confidence: 99%